Nuclease Production and Lysostaphin Susceptibility of Staphylococcus aureus and Other Catalase-Positive Cocci - Lachica, R. V. F. (1971)
Some strains of Staphylococcus epidermidis and Micrococcus sp. produce nucleases. However, thermal stability was shown to be unique to the nucleases of S. aureus. In addition, two micromethods for susceptibility testing to lysostaphin were more precise and convenient than anaerobic glucose fermentation in distinguishing between the genera Staphylococcus and Micrococcus.